PERANCANGAN AKSESORIS MOTOR UNTUK MENINGKATKAN KEAMANAN BERKENDARA - Cherry; Widodo, Lamto; Gozali, Lina (Jurnal Mitra Teknik Industri, 2023)
Turn signal lights or rearview mirror are useful as markers when you want to turn right and left when you are at a corner, a T-junction, or an intersection. By turning on one side of the light, namely the right or left, it gives information to the riders behind and in front that you want to turn. Several factors can cause motorists to forget to turn off the turn signal, such as lack of concentration or the color of the turn signal during the day is less visible. Turn signal lights that stay on can confuse other motorists. Confusion of other drivers can break the concentration of road users and cause traffic accidents. With the aim of researching the causes of turn signal lights that keep on and confuse other people, a questionnaire was distributed to motorists. The research method used is AHP by distributing questionnaires to motorists and the result is the design of a 'Smart Light Spion' for the development of motorcycle accessories.